Causalidade e contraste em artigo de opinião: uma intervenção pedagógica funcionalista no ensino fundamental - Ferreira, Ana Carla de Sousa (2024)
In this research, we focus on the relations of causality and contrast mobilized in the opinion article genre, through a functionalist pedagogical intervention in a 9th grade class. We aim to investigate the contributions of the linguistic elements of cohesion by connection that establish relationships of causality and contrast from a functional perspective to the development and improvement of the argumentative competence of those students. Our theoretical support is the North American Functional Linguistics (Givón, 1995; Furtado da Cunha; Bispo, 2013) and its correlation with Portuguese language teaching as outlined in Bispo, Cordeiro e Lucena (2022). We also mobilized contributions from Textual Linguistics, notably based on Koch (2003, 2010) and Antunes (2005), and Argumentative Semantics, according to Ducrot (1977). Methodologically, this research is predominantly qualitative in nature, involving descriptive and explanatory aspects. The descriptive nature is related to the characterization of the linguistic elements mapped in the students' textual productions, as well as the treatment given to these elements by traditional grammars, based on a bibliographical survey. The explanatory aspects are due to the analysis and interpretation of the material generated in the intervention process. As results, we highlight that the students (a) used the items pois (because) and mas (but) more frequently than the other ones in the two versions of the opinion article when establishing causal and contrastive relationships, respectively, a fact which we relate to the principles of iconicity and marking; (b) used cohesive elements of causality and contrast in an appropriate manner, from a semantic-pragmatic point of view, in the two versions of the article; (c) in the last version, they managed to improve the writing of the opinion article, in terms of structural and linguistic aspects, based on the revision and rewriting carried out, although some weaknesses remained. We therefore conclude that the didactic sequence applied gave the students a new view of the use of cohesive elements of causality and contrast and the need to adapt them to the communicative event. We can also observe the importance and positive effects of approaching grammar topics from a functionalist perspective associated with official curriculum guidelines. This perspective gave the teacher-researcher the opportunity to explore with her students linguistic mechanisms by connection in authentic texts, explaining the functionality of these elements in textual organization, in the construction of meanings and in the argumentative direction of opinion articles.